Eat what with who - Seetoh, Stella Wai Yeng (Nanyang Technological University, 2021)
is a digital dining table and everyone is invited to join. This film dives into the colourful, bizarre world of gastronomic voyeurism – following a social phenomenon that takes root from food porn, modernity and new online behaviours. Along with the rest of the world, mukbang is now part of the Singaporean youth online diet and it is characteristic of our relationship with food, culture and technology.